Multicultural Education in Canadian Preservice Programs: Teacher Candidates’ Perspectives - Mujawamariya, Donatille; Mahrouse, Gada (Alberta Journal of Educational Research, 2004)
This report examines Canadian teacher candidates' perspectives on the multicultural education component of the preservice teacher education program they attend. The data analyze were collected through a questionnaire that set out to explore whether teacher candidates were satisfied with the multicultural education preparation they received and their ideas on how it might be improved. We present the findings in two parts. First we consider the teacher candidates' critiques and suggestions on multicultural education to reveal that the majority of respondents did not feel adequately prepared to the challenge teaching in ethno-racially diverse classrooms. Their responses point to specific programmatic and structural shortcomings of current multicultural curricula in Canadian teacher education programs. They suggest ways to improve the multicultural education curriculum including compulsory courses, more diversity among faculty and teacher candidates in the program, and an integrative approach across the teacher education curriculum. We then analyze the discourses embedded in their responses to examine how multicultural education is being understood by teacher candidates. Here we show that common understandings are often articulated through the paradigm of difference, through which the problems and the solutions are believed to be about the Other. We argue that these understandings promote rather than disrupt practices that sustain white hegemony. The article concludes with a discussion of the practical implications.